1991
DOI: 10.1524/ract.1991.5253.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Studies of Transuranium Elements for Nuclear Waste Disposal: Principles and Overview

Abstract: Data on radionuclide solubility can be important for the performance assessment of potential nuclear waste storage sites. Radionuclide solubility studies in groundwaters from a repository region will provide limits on radionuclide concentrations in these waters. Meaningful thermodynamically defined solubility studies must satisfy four criteria: (1) solution equilibrium conditions, (2) effective and complete phase separation, (3) a welldefined solid phase, and (4) knowledge of the speciation/oxidation state of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 11 publications
2
41
0
Order By: Relevance
“…The concentrations of dissolved neptunium corresponding to equilibrium with these phases are 7.791 x lo4 and 8.202 x lo4 molal, respectively. The calculated concentrations for Np205, NaNp0,C03:3.5H,0, and Np0,OH are all close to the values observed by Nitsche (1991).…”
Section: Molal (8702% Npoc) Suchsupporting
confidence: 83%
“…The concentrations of dissolved neptunium corresponding to equilibrium with these phases are 7.791 x lo4 and 8.202 x lo4 molal, respectively. The calculated concentrations for Np205, NaNp0,C03:3.5H,0, and Np0,OH are all close to the values observed by Nitsche (1991).…”
Section: Molal (8702% Npoc) Suchsupporting
confidence: 83%
“…The Np(OH), or Pu(OH), neutral species concentration in water, which can be calculated from the s,olubi.lity product, SP, Pennernan et al 1961;and Nitsche 1991), is lower than the solubilities found in NaOH by a factor of about l@. Consequently, the An(OH), concentration is negligible relative to the hydroxo complex concentration.…”
Section: Whc-ep-0897mentioning
confidence: 99%
“…Nitsche (1991) provides a useful general summary of the principles and techniques of solubility studies. A large number of techniques have been used to characterize the aqueous speciation of radionuclides.…”
Section: Solubility and Speciationmentioning
confidence: 99%